PENGARUH MODEL PEMBELAJARAN SAVI UNTUK KETERAMPILAN MENARI PESERTA DIDIK SEKOLAH DASAR - Nur Rizki, Shyffa; Irna Khaleda Nurmeta; Din Azwar Uswatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model on the dancing skills of elementary school students. The research design used in this study is the Non-equivalent Control Group Design design. The sampling technique used is a saturated sample (census). In this study, the sample used was all fifth grade students of SDN Palasari with a population sample of 34 students divided into 17 students in each group, namely the control group and the experimental group, not selected randomly. The test used in this study was to use the performance of dance skills with 4 indicators measured in this study, namely wiraga, wirama, wirasa and memory. The data analysis technique used a paired sample t-test which had previously been known for its homogeneity and normality. In the experimental group, the average pretest score was 45.59 and the average posttest score was 71.69. While in the control group, the average pretest score was 43.75 and the average posttest score was 48.16. The results of the hypothesis test obtained a sig. value of 0.001 because the sig. value <0.05 means that H0 is rejected and H1 is accepted, therefore there is a significant influence in the use of the SAVI learning model on the dancing skills of students in grade V.